Operator exposure to x-ray in left and right radial access during percutaneous coronary procedures: OPERA randomised study. Issue 7 (23rd January 2013) - Dominici, Marcello; Diletti, Roberto; Milici, Caterina; Bock, Carlo; Placanica, Attilio; D'Alessandro, Gianluigi; Arrivi, Alessio; Italiani, Marco; Buono, Eduardo; Boschetti, Enrico
Abstract : Objective: Left radial access (LRA) and right radial access (RRA) have been shown to be safe and effective for coronary arteries catheterisation. However, the differences between the two approaches in terms of radiation exposure are still unclear. The aim of the present investigation is to evaluate in a randomised study, the dose of radiation absorbed by operators using either LRA or RRA. Design: Randomised, prospective, double arm, single centre study. Setting: University Hospital. Patients: Male or female subjects with stable, unstable angina and silent ischaemia. Interventions: The present study is a comparison of LRA and RRA for coronary artery catheterisation in terms of operators' radiation exposure. Main outcome measures: The primary outcome measure was the radiation dose absorbed by operators; secondary outcome measures were fluoroscopy time, dose-area product and contrast delivered. Results: A total of 413 patients were enrolled; 209 were randomly selected to undergo diagnostic procedures with RRA and 204 with LRA. The operator's radiation exposure was significantly lower in the left radial group (LRA 33±37 μSv vs RRA 44±32 μSv, p=0.04). No significant differences were observed in  fluoroscopy time (LRA 349±231s vs RRA 370±246 s p=0.09) and dose-area product (LRA 7011.42±3617.30 μGym 2 vs RRA 7382.38±5226.61 μGym 2, p=0.80), even though in both there was a trend towards a lower level in the LRA. No differences were observed in contrast medium delivered (LRA 89.92±32.55 ml vs RRA 88.88±35.35 ml, p=0.45). Conclusions: The LRA was associated in the present report with a lower radiation dose absorbed by the operator during coronary angiography.